2015
DOI: 10.1016/j.celrep.2015.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Aubergine iCLIP Reveals piRNA-Dependent Decay of mRNAs Involved in Germ Cell Development in the Early Embryo

Abstract: SummaryThe Piwi-interacting RNA (piRNA) pathway plays an essential role in the repression of transposons in the germline. Other functions of piRNAs such as post-transcriptional regulation of mRNAs are now emerging. Here, we perform iCLIP with the PIWI protein Aubergine (Aub) and identify hundreds of maternal mRNAs interacting with Aub in the early Drosophila embryo. Gene expression profiling reveals that a proportion of these mRNAs undergo Aub-dependent destabilization during the maternal-to-zygotic transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 49 publications
7
164
1
Order By: Relevance
“…Interestingly, 20 proteins in the zebrafish MZT mRBPome were not previously detected by mRNA interactome capture in mammalian cells (Supplemental Table S3), indicating potential embryo-specific mRNA association. Indeed, this group includes proteins with restricted expression and/or elevated functions during early embryogenesis among which were embryonic poly(A)-binding protein (Pabpc1l) and cytoplasmic polyadenylation element binding protein (Cpeb1b), regulators of embryonic cytoplasmic mRNA polyadenylation (Charlesworth et al 2013); the paralog of the maternal-effect gene Zar1 (Wu et al 2003); and Btg4 and Piwi proteins, negative regulators of maternal mRNA stability in mouse oocytes and fly embryos, respectively (Barckmann et al 2015;Yu et al 2016). Finally, comparison of the preZGA and ZGA mRBPomes revealed 24 and 53 proteins that were specifically detected at preZGA and ZGA, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 20 proteins in the zebrafish MZT mRBPome were not previously detected by mRNA interactome capture in mammalian cells (Supplemental Table S3), indicating potential embryo-specific mRNA association. Indeed, this group includes proteins with restricted expression and/or elevated functions during early embryogenesis among which were embryonic poly(A)-binding protein (Pabpc1l) and cytoplasmic polyadenylation element binding protein (Cpeb1b), regulators of embryonic cytoplasmic mRNA polyadenylation (Charlesworth et al 2013); the paralog of the maternal-effect gene Zar1 (Wu et al 2003); and Btg4 and Piwi proteins, negative regulators of maternal mRNA stability in mouse oocytes and fly embryos, respectively (Barckmann et al 2015;Yu et al 2016). Finally, comparison of the preZGA and ZGA mRBPomes revealed 24 and 53 proteins that were specifically detected at preZGA and ZGA, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strong coupling between poly(A) tail length and translation efficiency (TE) has been observed in the cleavage embryos of many species (Subtelny et al 2014;Eichhorn et al 2016;Lim et al 2016), although the molecular mechanisms that enable this coupling remain unclear. Recent studies have begun to determine a variety of mechanisms through which maternal mRNA clearance is accomplished (Giraldez et al 2006;Tadros et al 2007;Lund et al 2009;Tadros and Lipshitz 2009;Barckmann et al 2015;Bazzini et al 2016;Mishima and Tomari 2016). An important role has been ascribed to the evolutionarily conserved miRNA, miR-430/427, that mediates translational repression and clearance of a subset of maternal mRNAs in zebrafish and Xenopus embryos during MZT (Giraldez et al 2006;Lund et al 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Piwi proteins are known to enlist germline-specific Piwi-interacting RNAs (piRNAs) to suppress transposable elements and protect the integrity of the genome in germ cells (Juliano et al, 2011; Siomi et al, 2011). We and others recently showed that the Piwi/piRNA machinery also functions in regulating protein coding genes in germ cells (Gou et al, 2014; Zhang et al, 2015; Barckmann et al, 2015; Watanabe et al, 2015; Vourekas et al, 2016). Extensive genetic studies in worms, flies, fish, and mice indicate that Piwi proteins are essential for gametogenesis in animals (Cox et al, 1998; Harris and Macdonald, 2001; Deng and Lin, 2002; Kuramochi-Miyagawa et al, 2004; Carmell et al, 2007; Houwing et al, 2008; Batista et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1a ) and germ plasm mRNAs 15,20 are uniformly distributed throughout tud embryos; therefore the observed loss of binding specificity towards posterior mRNAs in the absence of Tudor can only be attributed to the disruption of the germ plasm. Thus our experimental approach allows the identification of the mRNAs specifically bound by Aub in the germ plasm, irrespective of the function of Aub in the clearance of maternal mRNAs in the somatic part of the embryo 21,22 . To identify the primary mRNA targets of Aub within the germ plasm during the formation of germ cells, we calculated the rank product of the normalized lgClip values for mRNAs in the 12 posterior localization categories marked with an asterisk in Supplementary Table 3 , from three replicate yw embryo libraries (p-value <0.05).…”
mentioning
confidence: 99%